Fusing Facial Features for Face Recognition - Ahmad Dargham, Jamal; Chekima, Ali; Gubin Moung, Ervin (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2019)
Face recognition is an important biometric method because of its potential applications in many fields, such as access control, surveillance, and human-computer interaction. In this paper, a face recognition system that fuses the outputs of three face recognition systems based on Gabor jets is presented. The first system uses the magnitude, the second uses the phase, and the third uses the phase-weighted magnitude of the jets. The jets are generated from facial landmarks selected using three selection methods. It was found out that fusing the facial features gives better recognition rate than either facial feature used individually regardless of the landmark selection method.
Keywords: bunch graph; facial recognition; gabor filter; image processing; wavelet; IJIMAI